Estudos químicos e biológicos de fungos endofíticos de Gustavia sp. - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
CHEMICAL AND BIOLOGICAL STUDIES ON FUNGI endophytic from Gustavia sp. Endophytic fungi and bacteria are those living at least a period of their live into the intercellular spaces of plants colonizing all vegetal tissues without causing any apparent symptom. In order to obtain fungal metabolites in this work, the fungi were, first of all, collected, isolated, purified, identified (at least their genera) and preserved. From 384 plant-tissues fragments (leaf, stem, trunk and root) of Gustavia sp. 93 endophytic fungi had been isolated and 67 strains were preserved. Those strains were from seven genera (Fusarium, Xylaria, Pestalotiopsis, Penicillium, Cephalosporium, Aspergillus and Colletotrichum (Glomerella)) and some were ascomycetes. Chemical study began by chemical screening of 21 extracts of endophytic fungi representing each group isolated. On base in the bioassays of the extracts, four strains were selected to isolate bioactive metabolites. Three of thouse strains, Nectria setofusariae (400), Penicillium chrysogenum (401) and Xylaria adscendens (447), have been identified by rDNA sequencing. From their extracts, several chemical constituintes have been isolated: a mixture of piliformic acid and 5-carboxymelein from X. adscendens; the ergosterol peroxides in the endo and exo forms, a mixture of the bisorbicillinoids trichodimerol, dihydrotrichodimerol e tetrahydrotrichodimerol and the sterigmatocistin (STC), as well a mixture of fatty acids from P. chrysogenum; a mixture of the phenylacetic and 4-methoxyphenylacetic acids from Aspergillus sp.; and the fusaric and phenylacetic acids from N. setofusariae. Besides, mass spectrometry analysis have shown other sorbicillinoids components in an extract fraction from P. chrysogenum. 1D and 2D NMR spectroscopy and mass spectrometry have been used together with literature data for identify the metabolites. Citotoxic bioassays of the extracts, fractions and substances have shown high citotoxic potential against three tumoral strains form a fraction from N. setofusariae and the substance STC from P. chrysogenum. This work resulted in the discovery of a strain of P. chrysogenum producing metabolites of the class of bisorbicillinoids. This is the first report of these substances in studies of fungi from Brazilian Amazon and reveals the importance of such work to continue to operate this line.
Keywords: Fungos endofíticos; Gustavia; Bisorbicilinoides; Esterigmatocistina; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA: QUÍMICA ORGÂNICA